Engineering circuit analysis / by J. David Irwin, Robert Mark Nelms. - Irwin, J. David, 1939- (Wiley, 2011)
This reader-friendly book has been completely revised to ensure that the learning experience is enhanced. It is built on the strength of Irwin's problem-solving methodology, providing readers with a strong foundation as they advance in the field.